Aspect and coercion in ancient greek - Bary, Corien; Egg, Markus (Proceedings of the Amsterdam Colloquium, 2007)
The interpretations of aoristic and imperfective aspect in Ancient Greek cannot be attributed to unambiguous aspectual operators but suggest an analysis in terms of coercion in the spirit of de Swart (1998). But since such an analysis cannot explain the Ancient Greek data, we combine Klein’s (1994) theory of tense and aspect with Egg’s (2005) aspectual coercion approach. According to this theory, (grammatical) aspect relates the runtime of an eventuality and the current time of reference (topic time), whereas tense relates the moment of utterance and the topic time. These relations can trigger aspectual selection restrictions (and subsequent aspectual coercions) just like e.g. aspectually relevant temporal adverbials, and are furthermore susceptible to the Duration Principle of Egg (2005): properties of eventualities must be compatible with respect to the duration they specify for an eventuality, otherwise coercion is called for. The Duration Principle guides the selection between different feasible coercion operators in cases of aspectual coercion but can also trigger coercions of its own. We analyse the interpretations of aorist and imperfective as cases of coercion that avoid impending violations of aspectual selection restrictions or the Duration Principle, which covers cases that are problematic for de Swart’s (1998) analysis.